The Noetic Signature Inventory: Development, Exploration, and Initial Validation - Wahbeh, Helané; Fry, Nina; Speirn, Paolo (Frontiers in Psychology, 2022)
“Noetic” comes from the Greek word noesis, meaning inner wisdom or direct knowing. Noetic experiences often transcend the perception of our five senses and are ubiquitous worldwide, although no instrument exists to evaluate their noetic characteristics both within and between individuals. We developed the Noetic Signature Inventory (NSI) through an iterative qualitative and statistical process as a tool to subjectively assess noetic experiences. Study 1 developed and evaluated a 175-item NSI using 521 self-selected research participants, resulting in a 46-item NSI with an 11-factor model solution. Study 2 examined the 11-factor solution, construct validity, and test-retest reliability, resulting in a 44-item NSI with a 12-factor model solution. Study 3 confirmed the final 44-item NSI in a diverse population. The 12-factors were: 1. Inner Knowing; 2. Embodied Sensations; 3. Visualizing to Access or Affect; 4. Inner Knowing Through Touch; 5. Healing; 6. Knowing the Future; 7. Physical Sensations from Other People; 8. Knowing Yourself; 9. Knowing Other’s Minds; 10. Apparent Communication with Non-Physical Beings; 11. Knowing Through Dreams; and 12. Inner Voice. The NSI demonstrated internal consistency, convergent and divergent content validity, and test-retest reliability. The NSI can be used for future studies to evaluate intra- and inter-individual variation on these personal qualities.